﻿Beware of scientific scams! Hints to avoid predatory publishing in biological journals - Cássio Cardoso Pereira; Marco A. R. Mello; Daniel Negreiros; João Carlos Gomes Figueiredo; Walisson Kenedy-Siqueira; Lara Ribeiro Maia; Stephannie Fernandes; Gabriela França Carneiro Fernandes; Amanda Ponce de Leon; Lorena Ashworth; Yumi Oki; Gislene Carvalho de Castro; et al. (Neotropical Biology and Conservation, 2023)
Our motivation for writing this editorial is to alert the academic community about the risks of predatory publishing in Biology. By piggy-backing on the open access (OA) movement and taking advantage of the “publish or perish” culture in a system that prioritises quantity over quality, predatory publishing has grown exponentially in recent years and spread across all areas of knowledge. Thousands of predatory journals and books have emerged and (provided a fee is paid) they publish scientific papers and chapters without submitting them to rigorous peer review. Now there are even predatory meetings, which promise to accept talks and publish complete works for a fee, also without reviewing them properly. These profit-making machines can damage both academia and society, putting at risk the quality of science and public trust in it, the well-being of the population, the conservation of biodiversity and the mitigation of climate change. We show the modus operandi behind invitations to contribute to predatory journals, books and meetings and suggest ways to separate the wheat from the chaff. Finally, we discuss the need to create regulatory agencies that perform a careful and systematic evaluation of the activities carried out by publishers.